Nothing much for kinds - Husband, EM (Linguistics Department, Queen Mary University of London, 2022)
Whether the kind/object distinction is grammatically encoded or extra-grammatical in nature has been up for debate. This paper reviews a recent grammatical approach by Borik & Espinal (2012) that proposes that grammatical number also encodes a realization operator, a kind-to-object type-shift, with reference to kinds ultimately deriving from numberless definites and subkind interpretations emerging from a predicatedriven object-to-subkind type-shift. I argue that this approach to subkinds suffers faces conceptual and empirical challenges, focusing particularly on the unavailability of subkind interpretations for English mass quantifiers and Dutch mass diminutives which reveals their deep connection to the count system of the grammar. I propose severing grammatical number and realization, with the latter emerging from its own functional structure, DimP. After adopting this analysis, I demonstrate that several other constructions cross-linguistically appear to behave like English mass quantifiers or Dutch diminutives and propose a typology, suggesting that two possible but unattested grammatical patterns fail to emerge because no language has a dedicated functional structure for kind interpretation. Ultimately, this analysis proposed suggests that we are cognitively constituted to think about kinds as types that are independent of their token objects and grammatically structured to encode a kind type inside nominals, even those that are object-referring.